Comparison of three molecular diagnostic assays for SARS‐CoV‐2 detection: Evaluation of analytical sensitivity and clinical performance. Issue 2 (12th January 2022) - Kim, Ha Nui; Yoon, Soo‐Young; Lim, Chae Seung; Yoon, Jung
Abstract: Background: Currently, SARS‐CoV‐2 RNA detection using real‐time reverse‐transcription PCR (rRT‐PCR) is the standard diagnostic test for COVID‐19 infection. Various rRT‐PCR assays are currently used worldwide, targeting different genes of the SARS‐CoV‐2. Here, we compared the analytical sensitivity and clinical performance (sensitivity and specificity) of Allplex SARS‐CoV‐2/FluA/FluB/RSV assay (Seegene), Standard M nCoV real‐time detection kit (SD Biosensor), and U‐TOP COVID‐19 detection kit (Seasun Biomaterials) for SARS‐CoV‐2 detection. Methods: Two hundred and forty‐nine nasopharyngeal swab samples were evaluated to compare the clinical performance of the rRT‐PCR assays. For the analytical performance evaluation, two RNA controls with known viral loads—SARS‐CoV‐2 RNA control and SARS‐COV‐2 B.1.351 RNA control—were used to investigate the potential impact of SARS‐CoV‐2 variants, particularly the B.1.351 lineage. Results: Limits of detection ranged from 650 to 1300 copies/ml for rRT‐PCR assays, and the mean differences in cycle threshold (C t ) values of the two RNA controls were within 1.0 for each target in the rRT‐PCR assays (0.05–0.73), without any prominent C t value shift or dropouts in the SARS‐COV‐2 B.1.351 RNA control. Using the consensus criterion as the reference standard, 89 samples were positive, whereas 160 were negative. The overall clinical performance of rRT‐PCR assays was comparable (sensitivity 98.88%–100%; specificity 99.38%–100%), whereas the sensitivities of each target gene were more variable. Conclusions: The three rRT‐PCR assays showed comparable analytical sensitivity and clinical performance. The analytical and clinical sensitivities of each target gene were influenced more by the primer and probe design than the target gene itself. Abstract : For the analytical performance evaluation, two RNA controls with known viral loads—SARS‐CoV‐2 RNA control and SARS‐COV‐2 B.1.351 RNA control—were used to investigate the potential impact of SARS‐CoV‐2 variants, particularly the B.1.351 lineage. Limits of detection ranged from 650 to 1300 copies/ml for rRT‐PCR assays and the mean differences in cycle threshold (C t ) values of the two RNA controls were within 1.0 for each target in the rRT‐PCR assays (0.05–0.73), without any prominent C t value shift or dropouts in the SARS‐CoV‐2 B.1.351 RNA control. The overall clinical performance of rRT‐PCR assays was comparable (sensitivity 98.88%–100%; specificity 99.38%–100%), whereas the sensitivities of each target gene were more variable. Both analytical and clinical performances of each target gene appear to be influenced more by the primer and probe design rather than the target gene. Clinical performance results were in line with the analytical sensitivity results. The S and ORF1ab genes were the most sensitive target genes using the Allplex SARS‐CoV‐2/FluA/FluB/RSV assay and U‐TOP COVID‐19 detection kit. In the case of the Standard M nCoV real‐time detection kit, although the difference in analytical sensitivity was not evident, RdRp showed higher sensitivity than the E gene.